Exploring the Work–Life Balance of Elementary Educator-Mothers in the Second and Third Districts of Masbate - Favila, Mary Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the work–life balance of elementary educator-mothers in Masbate’s Second and Third Districts, focusing on their management practices, influencing factors, and encountered challenges. Anchored on Role Theory, Work–Family Border Theory, and Conservation of Resources Theory, the research employed a quantitative descriptive–correlational design. Data were collected from 47 educator-mothers through a validated researcher-made questionnaire using a four-point Likert scale. Descriptive statistics (frequency, percentage, weighted mean) and inferential analysis (Pearson r at 0.05 level of significance) were used to analyze the data. Findings revealed that most respondents were married, aged 26–30, pursuing master’s degree units, and had 6–10 years of teaching experience. The respondents demonstrated strong work–life balance practices, particularly in time management, coping strategies, involvement in school-related activities, and participation in family responsibilities. Despite these strengths, they experienced significant challenges, including workload demands, conflicts between school and family responsibilities, financial pressures, limited personal time, and feelings of exhaustion. The study also found a weak but statistically significant relationship between demographic profile and perceived work–life balance, indicating that demographic factors slightly influence role management. The study concludes that while educator-mothers effectively manage their dual roles through adaptive strategies, institutional and contextual challenges persist. It recommends enhanced institutional support, including manageable workloads, wellness programs, flexible arrangements, and policies responsive to teachers’ demographic conditions. This study aligns with SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), SDG 5 (Gender Equality), and SDG 8 (Decent Work and Economic Growth) by addressing teacher well-being, gendered role expectations, and working conditions in the education sector. It contributes to sustainability by informing institutional and educational practices that support teacher welfare, improve instructional quality, and promote balanced socio-economic roles among working mothers.